In Vitro Study on Actinomycetes Extracts Against The Stem Bleeding Disease of Coconut: Antifungal Studies - Nisha, M. M.; Kumar, S. Santhosh; Ibomcha, N.; Susmitha, S.; Muddukrishna, B. V. (International Coconut Community, 2022)
Several compounds produced by Actinomycetes group of bacteria have proven potential in inhibiting plant pathogenic fungi. In the present study, two microbial ethyl acetate extracts from Streptomyces were tested for their antifungal properties against Thielaviopsis paradoxa, the causal organism of stem bleeding disease in coconut. The cultural filtrates of 2 strains of Streptomyces (AFL-1 and AFL-2) were extracted with Ethyl acetrate. The resulting ethyl acetate extract of AFL-1 showed complete in-vitro inhibition of fungal growth at relatively low concentrations (0.25%) while Ethyl ecetate extract of AFL-2 needed higher concentrations (over 0.5%) to eliminate pathogen growth. This finding indicate their potential and further exploitation as biopesticides for the control of deadly pathogen T. paradoxa.